2008
DOI: 10.1155/2008/782358
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis of Ag and Pd Nanospheres, Nanowires, and Nanorods Using Vitamin B2: Catalytic Polymerisation of Aniline and Pyrrole

Abstract: For the first time, we report green chemistry approach using vitaminB2in the synthesis of silver (Ag) and palladium (Pd), nanospheres, nanowires, and nanorods at room temperature without using any harmful reducing agents, such as sodium borohydride (NaBH4) or hydroxylamine hydrochloride and any special capping or dispersing agent. VitaminB2was used as reducing agent as well as capping agent due to its high-water solubility, biodegradability, and low-toxicity compared with other reducing agents. The average par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(21 citation statements)
references
References 50 publications
0
20
0
1
Order By: Relevance
“…22,23 The choice of solvent, reducing and/or capping agent for the synthesis of metal nanocomposite plays an important role for such greener approach and make the methodology an important finding to the scientific world. [24][25][26][27][28] Table S1 summarizes some literature data on the particle size of the Ag and Pd nanoparticles depending on the green synthesis conditions and the bio-materials used and finally compared with our work.…”
Section: Introductionmentioning
confidence: 99%
“…22,23 The choice of solvent, reducing and/or capping agent for the synthesis of metal nanocomposite plays an important role for such greener approach and make the methodology an important finding to the scientific world. [24][25][26][27][28] Table S1 summarizes some literature data on the particle size of the Ag and Pd nanoparticles depending on the green synthesis conditions and the bio-materials used and finally compared with our work.…”
Section: Introductionmentioning
confidence: 99%
“…Adicionalmente, o tamanho médio das NPOs foi de 6,1±0,1 nm e das nanopartículas de paládio foi de 4,1±0,1 utilizando rotas de síntese semelhantes. Também foi demonstrado que a forma e tamanho das NPMs são dependentes do solvente utilizado na síntese 46 .…”
Section: Vitaminasunclassified
“…Vitamins and amino acids provided tremendous opportunities in the synthesis of NPs intended for therapeutic applications [82]. Nadagouda et al demonstrated the reducing as well as capping potential of vitamin B 2 in the synthesis of AgNPs and palladium NPs [83]. More practical synthesis of the NPs should be accompanied by an easily available source which should be nontoxic, nonhazardous, nonvolatile, biodegradable and biocompatible in nature.…”
Section: Biomolecule Mediated Synthesis Of Metallic Npsmentioning
confidence: 99%